2019
DOI: 10.1055/s-0039-1692652
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knee Kinematics and Kinetics during Stair Descent in Single- and Multi-Radius Total Knee Arthroplasty

Abstract: Despite continuing advances, nearly 20% of patients remain dissatisfied with their total knee arthroplasty (TKA) outcomes. Single-radius (SR) and multiradius (MR) TKA designs are two commonly used knee replacement designs based on competing theories of the flexion/extension axis of the knee. Our aim was to characterize stair descent kinematics and kinetics in SR and MR TKA subjects. We hypothesized that 1 year after TKA, patients who received SR TKA will more closely replicate the knee kinematics and kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, abruptly moving from a large to a small radius during mid‐flexion was claimed to lead to transient collateral ligament slackness and paradoxical anterior translation of the femur 16 . A single‐radius (SR) and gradually increasing radius (G‐curve) design were introduced to address this mid‐flexion instability, which studies have suggested allow for more normal kinematics compared to the J‐curve design 17‐21 . No long‐term outcome studies have confirmed the superiority of these designs over the J‐curve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, abruptly moving from a large to a small radius during mid‐flexion was claimed to lead to transient collateral ligament slackness and paradoxical anterior translation of the femur 16 . A single‐radius (SR) and gradually increasing radius (G‐curve) design were introduced to address this mid‐flexion instability, which studies have suggested allow for more normal kinematics compared to the J‐curve design 17‐21 . No long‐term outcome studies have confirmed the superiority of these designs over the J‐curve.…”
Section: Introductionmentioning
confidence: 99%
“…16 A single-radius (SR) and gradually increasing radius (G-curve) design were introduced to address this mid-flexion instability, which studies have suggested allow for more normal kinematics compared to the J-curve design. [17][18][19][20][21] No long-term outcome studies have confirmed the superiority of these designs over the J-curve. Despite this, tibial component geometry likely plays a larger role in knee kinematics, as illustrated by the very different constraints provided by surfaces with low and high conformity.…”
mentioning
confidence: 99%